Factors Associated with Choking During Meals; a Risk Indicator for Repetitive Fevers in The Elderly Community - Nishiyama, Takeshi; Nagata, Emi; Oho, Takahiko (Makara Journal of Health Research, 2017)
Background: Choking during meals is a common symptom in the elderly, however the factors associated with it have not been fully clarified. In this study, we examined the factors associated with choking during meals. Methods: The oral health status and practices that promote oral health conditions was surveyed in 1305 community dwelling elderly using a self-administered questionnaire. Eight items including satisfaction with their oral condition, denture fit, chewing ability, tooth brushing frequency, dental visits, exercises to train muscles for chewing and swallowing, choking during meals, and repetitive fever were selected for analysis. Results: 25.1% of the subjects experienced choking during meals, which was significantly associated with repetitive fever occurrence. Differences in satisfaction levels with their oral condition, denture fit, chewing ability, and tooth brushing frequency were observed between groups with and without choking. Age, satisfaction level, and chewing ability were significantly associated with choking during meals. Conclusions: This study demonstrated that choking during meals is a risk indicator for repetitive fever in the elderly living in community settings. Poor chewing ability and dissatisfaction with their oral condition were risk factors associated with choking. These results suggest that training the elderly to eat efficiently and safely and improving oral conditions is necessary for those who suffer from choking during meals to prevent repetitive fever.